Microfluidic-enhanced 3D bioprinting of aligned myoblast-laden hydrogels leads to functionally organized myofibers in vitro and in vivo. (July 2017) - Costantini, Marco; Testa, Stefano; Mozetic, Pamela; Barbetta, Andrea; Fuoco, Claudia; Fornetti, Ersilia; Tamiro, Francesco; Bernardini, Sergio; Jaroszewicz, Jakub; Święszkowski, Wojciech; Trombetta, Marcella; Castagnoli, Luisa; et al.
Abstract: We present a new strategy for the fabrication of artificial skeletal muscle tissue with functional morphologies based on an innovative 3D bioprinting approach. The methodology is based on a microfluidic printing head coupled to a co-axial needle extruder for high-resolution 3D bioprinting of hydrogel fibers laden with muscle precursor cells (C2C12). To promote myogenic differentiation, we formulated a tailored bioink with a photocurable semi-synthetic biopolymer (PEG-Fibrinogen) encapsulating cells into 3D constructs composed of aligned hydrogel fibers. After 3–5 days of culture, the encapsulated myoblasts started migrating and fusing, forming multinucleated myotubes within the 3D bioprinted fibers. The obtained myotubes showed high degree of alignment along the direction of hydrogel fiber deposition, further revealing maturation, sarcomerogenesis, and functionality. Following subcutaneous implantation in the back of immunocompromised mice, bioprinted constructs generated organized artificial muscle tissue in vivo . Finally, we demonstrate that our microfluidic printing head allows to design three dimensional multi-cellular assemblies with an exquisite compartmentalization of the encapsulated cells. Our results demonstrate an enhanced myogenic differentiation with the formation of parallel aligned long-range myotubes. The approach that we report here represents a robust and valid candidate for the fabrication of macroscopic artificial muscle to scale up skeletal muscle tissue engineering for human clinical application.